Rapidly progressing necrotizing fasciitis with chickenpox infection: A case series - Fereshteh Moshfegh; Zahra Hosseinzade; Seyed Hamid Salehi; Mohammad Javanbakht; Ali Manafi Anari; Behnam Sobouti (Elsevier, 2025)
Introduction: Varicella usually resolves without complications. However, there is a risk of necrotizing soft tissue infections such as necrotizing fasciitis (NF) that can complicate the management. Case series: Case 1 was a 5-year-old male who developed widespread vesicular lesions and fever, diagnosed as varicella. His condition worsened as he presented with abdominal distension and pain, leading to hospitalization for suspected toxic shock syndrome. Computed tomography (CT) of the chest and abdomen revealed features consistent with NF, prompting extensive debridement and subsequent vacuum-assisted closure (VAC) therapy. After several surgical revisions he underwent skin grafting and was eventually discharged home. Case 2 was a 4.5-year-old male with no significant medical history, who presented with generalized fever, neck pain, and rapidly spreading skin rashes. He subsequently developed severe acute idiopathic scrotal edema and extensive ecchymosis, requiring immediate hospitalization. Broad-spectrum antibiotics were started. He underwent emergent wide debridement of the ecchymotic areas. The pathology analysis confirmed necrotic tissue, and cultures were positive for bacteria and fungi. He underwent repeated debridement. The last debridement was followed by uncontrollable hemorrhage, and he passed away. Conclusion: While varicella is generally a mild disease, life-threatening complications such as necrotizing fasciitis can occur.